(untitled) (Foro de Educacion, 2023)
The objective of this article is to analyze how the public university has been conceived and treated by the federal government from the impeachment of President Dilma Rousseff, especially through a narrative that depreciates it in terms of its role and performance, attributing to it a certain sense or meaning. The Brazilian university is going through a difficult moment in its history, as it has been suffering constant budget cuts, compromising its operational condition, a situation aggravated by the pandemic of the new coronavirus. In Brazil, we assume that the denialism observed constitutes a deliberate strategy with the objective of weakening and disqualifying the critical and reflective thinking that puts in check the advancement of the interests of global financial capital. It serves a broader project, a form of social, economic and cultural existence of a neoliberal nature imbricated in a geopolitics of knowledge that favors certain interests of certain groups and nations. Such a project therefore implies the defense of a worldview that must be established as the correct view of the mode of existence. It is the defense of single thought. Although in practice its autonomy is more illusory than real, it is a fact that, when the university makes use of this freedom, when it «bothers», it is that it suffers the attacks of certain groups, especially those who are in a position of strategic decision, like governments, and perceive criticism as a threat to certain interests.